Knowledge, Capabilities and Human Capital Formation in Economic Growth - Paul A. David (New Zealand Government, The Treasury, 2000)
This monograph, which has been prepared as a Research Report to the New Zealand (New Zealand) Treasury, undertakes three main tasks: (1) describing the various forms of tangible and intangible human capital, their relationship to "capabilities" affecting human well-being, and the channels through which they may contribute to economic growth; (2) reviewing the major theoretical and empirical findings on the microeconomic determinants, and macroeconomic growth effects of investment in human capital; (3) reviewing salient general implications for policies affecting human capital, and indicating measures specifically germane to the situation of the New Zealand economy. For these purposes, the concept of human capital is defined comprehensively, so that it embraces capacities for interpreting flows of sensory data and structured information required for goal-directed individual actions and inter-personal transactions, and for providing various physical labour service- inputs in ordinary production processes. More conventionally, it subsumes the creative faculties for generating new scientific and technological knowledge, the cognitive basis of entrepreneurship, and the competences for managing market and non-market production as well as household consumption activities. The report is organised in three main Parts that address the three major objectives, taking each in its turn. A detailed Table of Contents and an Executive Summary precede the text, which is followed by extensive bibliographic references. A unifying conceptual framework is developed to (a) identify the micro-level processes involved in human capital formation; (b) implicitly aggregate the resulting qualities and capabilities of individuals belonging to successive population cohorts; (c) trace the interrelated influences that the forms of human capital have upon macroeconomic performance. The review of empirical evidence at the macroeconomic level features a discussion of the deficiencies of data and methods in many of the international cross-section studies, and contrasts recent econometric findings on the role of education in economic growth among the developed economies with the conclusions derived through more detailed analyses of their historical experiences. Significant policy implications do emerge from the modern macroeconomic growth literature, but these are very broad in nature and not particularly germane to the situation of small, open economies that may lack a substantial industrial base or the extensive human and institutional infrastructure required to generate the knowledge-base needed for their peoples' well-being and their firms' competitive success in international markets. Nor does the received literature adequately treat the implications of such economies' potential to rapidly alter their respective human resource endowments through differential population migration. Consideration of human capital policies geared more closely to the specific challenges and opportunities facing New Zealand's economy leads to the formulation of a number of novel proposals. These would reform tax treatment of education and training investments by residents and immigrants alike; subsidise new voluntary institutions developing on-the-job training programs under industry sponsorship; undertake public information infrastructure investments in order to reduce the costs of effective access to global knowledge bases in science and technology. Proposals also are considered for integrated government programmes to accelerate the closing of persistent socio-economic disparities within New Zealand society, such as those between Maori and non-Maori.
Keywords: H24; I28; J24; N30; O15; O38; 330; human capital; capabilities; knowledge; education; on-the-job training; R&D; productivity; macroeconomic growth theory; investment taxation and subsidies